Representasi Kemuliaan Seorang Ibu Perspektif Budaya Madura dalam Puisi D. Zawawi Imron: Kajian Semiotika Roland Barthes - Mubarok, Hayyul; Setya Yuwana Sudikan; Suhartono (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study reveals the representation of the nobility of a mother in poetry by D. Zawawi Imron through the perspective of Madurese culture with Roland Barthes’ semiotic approach. The analyzed poems, especially the poem entitled "Mother", represent the figure of the mother not only as a family figure, but also as closely attached to the cultural values of Madurese society. The method used to describe this is descriptive qualitative which is a process of analyzing data through logical descriptions. The results of the study show that (1) denotatively and connotatively, the mother is depicted as a noble, steadfast, and sacrificial figure, in line with the noble values of Madurese culture that uphold the steadfastness and honor of women as the pillars of the family; (2) mythologically, the mother is represented as a symbol of the homeland, spiritual strength, and cultural identity that is rooted in Madurese society. D. Zawawi Imron’s poetry is not only a personal expression of the figure of the mother, but also a collective reflection of Madurese culture on traditional morals and ethics.